Publishing journal articles - Becker, Lucinda M., 1963-; Denicolo, Pam. (Los Angeles, [Calif.] ; London : SAGE, 2012)
Practical, no-nonsense, accessible guide to planning, writing and publishing a journal article.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Academic writing